Pengaruh Media Augmented Reality dan Power Point Terhadap Hasil Belajar Sejarah di SMA Negeri 11 Kupang - Samuel Hendriko Selan; Dr. Djakariah, M.Pd; Jefriano Mali, S.Pd.,M.Pd (LPPM Institut Pendidikan Nusantara Global, 2026)
Due to low learning outcomes (60% of students below the Minimum Competency (KKM) of 75) brought on by the predominance of traditional lecture methods, the purpose of this study is to compare the effects of PowerPoint and Augmented Reality (AR) on the history learning outcomes of eleventh-grade students at SMA Negeri 11 Kupang. By using a quantitative approach and a quasi-experimental pre-test-post-test control group design, the population of 75 eleventh-grade students was divided into two groups, each consisting of 25 students, using cluster random sampling: experimental (AR) and control (PowerPoint). Examined using the Kolmogorov-Smirnov normality test, Levene's homogeneity test, independent t-test (SPSS), and N-Gain test. In terms of inter-group improvement, the experimental group showed better performance than the control group (pretest 60.4→posttest 83.6; gain 23.2; N-Gain 0.59, moderate), while the control group showed lower improvement (pretest 59.8 → posttest 74.2; gain 14.4; N-Gain 0.36, moderate). The independent t-test results showed a significant difference between the two groups (p = 0.000 < 0.05). In conclusion, augmented reality is advised for secondary school since it is more successful than PowerPoint at enhancing comprehension, motivation, and participation in history learning.